Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1097/00005344-200206000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Trough-to-Peak Ratio, Smoothness Index, and Circadian Blood Pressure Profile After Treatment With Once-Daily Fixed Combination of Losartan 100 and Hydrochlorothiazide 25 in Essential Hypertension

Abstract: The once-daily fixed combination of losartan 100 mg/hydrochlorothiazide 25 mg was evaluated for safety and efficacy in a multicenter open study by using 24-h ambulatory blood pressure monitoring in untreated patients with moderate-to-severe essential hypertension or patients with uncontrolled hypertension despite treatment with monotherapy or low-dose combination. After a 2-week washout period, 41 patients (22 men, 19 women) aged 34-74 years, showing a mean daytime blood pressure > 135/85 mm Hg, were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
11
0
2
Order By: Relevance
“…36,5558 Valsartan plus hydrochlorothiazide reported a similar trough-to-peak ratio (61%/57%) as that reported with valsartan alone in a previously described study (66%) 38,58. Therefore, the duration of action was not affected by the addition of another agent, although BP was lower with the combination treatment.…”
Section: Effect Of Increasing the Number Of Daily Antihypertensive Dosupporting
confidence: 75%
See 1 more Smart Citation
“…36,5558 Valsartan plus hydrochlorothiazide reported a similar trough-to-peak ratio (61%/57%) as that reported with valsartan alone in a previously described study (66%) 38,58. Therefore, the duration of action was not affected by the addition of another agent, although BP was lower with the combination treatment.…”
Section: Effect Of Increasing the Number Of Daily Antihypertensive Dosupporting
confidence: 75%
“… Note: Data from Coca et al,36 Coca et al,55 Kuschnir et al,56 Mancia et al,57 and Palatini et al58 Abbreviations: DBP, diastolic blood pressure; GITS, gastrointestinal therapeutic system; HCTZ, hydrochlorothiazide; SBP, systolic blood pressure.…”
Section: Figurementioning
confidence: 99%
“…22 In a study of untreated patients with moderate-to-severe essential hypertension or patients with uncontrolled hypertension despite treatment with monotherapy or low-dose combination, the response rate to losartan 100 mg/HCTZ 25 mg therapy was 87.8% (BP lowering 45 mm Hg of either 24 h SBP or 24 h DBP average values) after 8 weeks. 23 Current and prior clinical experience have shown that treatment with the losartan/HCTZ combination treatment can achieve clinically significant reductions of BP in Asian patients and that the magnitude of the reductions are consistent with those in non-Asian patients. Lower BPs are associated with reduced risk of cardiovascular events; 24 however, there are no end point studies carried out with losartan exclusively in Asian patients.…”
Section: Discussionmentioning
confidence: 88%
“…Die Kombination von Losartan und HCTZ wurde in zahlreichen Studien eingehend untersucht [9,15,21,33,34,37,41]. Es handelte sich hierbei um Patienten mit allen Schweregraden der Hypertonie, die unter der Monotherapie mit den einzelnen Komponenten nicht eingestellt werden konnten oder primär mit der Kombination behandelt wurden.…”
Section: Antihypertensive Wirksamkeit Und Verträglichkeitunclassified
“…Zusätzlich zur Behandlung mit Losartan ± HCTZ erhielten 54,1% der Patienten noch ein oder mehrere weitere Antihypertensiva. Der systolische/diastolische Blutdruck nahm von einem Ausgangswert von 158,1/90,3 mmHg nach 1-jähriger Behandlung auf 137,3/80,6 mmHg ab (8)(9)7 mmHg). Die Proportion der Patienten mit keiner/leichter/star ker kognitiver Beeinträchtigung betrug zu Beginn 30,0%/30,3%/39,7%, und zum Studienende 34,8%/28,1%/37,1%.…”
unclassified